Light mental representations of 11-12 year old students (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2013)
The light is a separate entity in the area, independent sources that produce it and the effects it causes during its spread. In several research focused on representations of light that are children from 5 to 15 years found that these representations are often incompatible with the scientific model. 112 (60 boys and 62 girls) participated in this research where we studied representations of children 11-12 years on the light. As a technique of research we chose the directive individual interview. The results of the research show that children of 11-12 years, use different categories of representations for the light.